Laboratory Study on The Use of Local Additive of Clam Shell in Water Based Mud - Nur Suhascaryo; Farrel M Dhaffa (Scientific Contributions Oil and Gas, 2024)
The use of clam shells as additives in water-based mud has gained attention as a natural material in drilling fluids. This study tested the physical properties and rheology of water-based mud with varying amounts of clam shells. The density of the mud after adding clam shell additives was determined using a mud balance, and the rheology was tested using a viscometer. Filtration volume and mud cake thickness were also tested using an LPLT (Low-Pressure, Low-Temperature) filter press for 30 minutes. The pH measurement was performed from the filtrate volume. The results showed that adding varying amounts of clam shell additives increased the density by 8.7 ppg, 8.9 ppg, and 9 ppg, respectively. The filtration loss and mud cake produced were considered good, with filtration loss and mud cake being 13 mL and 1.6 mm, 12.2 mL and 1.4 mm, and 10.4 mL and 1.3 mm, respectively. Clam shell can be used as a fluid loss reducer because it can affect the viscosity value of the mud, resulting in a low filtration loss value. Proportional to filtration loss: if the filtrate comes out a little, the resulting mud cake is thinner.